(untitled) (Research, Society and Development, 2021)
The objective of this work is to map academic production in relation to the theme of public Marketing. Thus, a theoretical framework was developed about public Marketing. The method adopted was a bibliometric research, targeting academic publications on the theme of public Marketing, in the main Administration events in the country (Semead, EnAnpad and EMA) and in the most recognized scientific bases worldwide (Web of Science, Scopus, Scielo) . The analysis of the theme of Public Marketing, allows an appreciation of the results aimed at citizens. Therefore, it was possible to identify that the theme of public Marketing, is little studied in depth by the academy. However, new studies are suggested in relation to the theme, in particular the use of Marketing by the public administration.